Caribbean Report 21-02-2000 - The British Broadcasting Corporation; Richards, Ken (anchor); Lake, Bernice (interviewee); Fraser, Tony (correspondent); de la Bastide, Michael Anthony (interviewee); Gordon, Orin (correspondent); Arthur, Owen (interviewee); Sawyer, Jerome (correspondent); Hall, Simeon (interviewee); Ingraham, Hubert (interviewee); Christie, Perry (interviewee); Josephs, Emma (correspondent); et al. (The British Broadcasting Corporation, 2000)
1. Headlines: (00:00-00:24) 2. Independent candidates could be the driving force behind the coalition that arises out of the general elections on March 3 in Anguilla. From a total of 18 nominated candidates, 8 are running as independents. Hubert Hughes, Chief Minister of the Anguilla United Movement is endorsing 2 candidates in the 7 seat race. (00:25-03:45) 3. Attorney General Ramesh Maharaj in Port-of-Spain mentions that the President of Trinidad and Tobago is creating delays for the government as the Panday administration assiduously tries to execute its decision. Two weeks later, Maharaj was advised by Basdeo Panday to create a Commission of Enquiry into the Judiciary. President Arthur Robinson has not yet signed the documents. This follows an almost identical constitutional impasse when President Robinson opposed the dismissal of two Tobago Senators. (03:46-05:32) 4. It is hoped that a documented account of issues among small states would determine the nature of their interaction with big international bodies such as the World Trade Organization. The decision was met made subsequent to a meeting between major multinational corporations and small states. The parameters set out problem areas from their vulnerability to natural disasters and the debilitating impact of unrestricted global trade on their economies. (05:33-07:10) 5. In the Bahamas, there has been an upsurge in violence. To date there have been 11 murders of which 9 of them were committed in the capital Nassau. There have been 7 violent deaths within a week period. This situation has created a cause for concern among citizens and police presence has been increased to intensify their crime fighting efforts. (07:11-09:37) 6. A warning has been issued by American climate scientists that predicts hurricane winds in North America and the Caribbean are getting more intense. Their research covers weather patterns as they have been monitored over 150 years. Scientists are predicting hurricanes to hit the Gulf of Mexico within the next 10 years. ...